People’s Economic Development Model based on Micro, Small, and Medium Enterprises (MSMEs) during Covid19 - Istiqomah, Nurul; Mafruhah, Izza; Noviani, Leni; Akbar, Leon; Ismoyowati, Dewi (Jurnal Penelitian Ekonomi dan Bisnis, 2022)
The aims of this study are analyzes the MSMEs business cycle based on the types of business in the COVID-19 pandemic, analyzes the supporting aspects in supporting the working system for MSMEs before and during the COVID-19 Pandemic, and analyzes MSMEs immunity. The findings of these three objectives will be used to formulate the MSME-based People's Economic Development Model. This study used a mixed method with a sequential explanatory model, where the researcher uses quantitative and qualitative methods sequentially. The quantitative method was carried out by analyzing the business cycle to determine the types of business according to the stages: peak, recession, depression or recovery so as to provide an overview of the pattern of MSME development. Result of this study are the MSMEs conditions during the COVID-19 pandemic can be divided into 4 quadrants: quadrant 1 Unable to market and unable to produce; quadrant 2, able produce but unable to market; quadrant 3, unable to produce but able to market; quadrant 4, able to produce and market. The role of stakeholders is divided into five actors, namely academics, business, government, society and mass media. The five actors together have their respective contributions to the development of MSMEs during the pandemic.Key words : MSME, Covid19, imunity, development model